Enhanced pro-apoptotic activity of rituximab through IBTK silencing in non-Hodgkin lymphoma B-cells - Vecchio, Eleonora; Marino, Rossana; Mimmi, Selena; Canale, Camilla; Caiazza, Carmen; Arcucci, Alessandro; Ruocco, Maria Rosaria; Schiavone, Marco; Santamaria, Gianluca; Palmieri, Camillo; Iaccino, Enrico; Mallardo, Massimo; et al. (Frontiers in Oncology, 2024)
Rituximab is a commonly used chemotherapeutic drug for patients with aggressive lymphomas, such as non-Hodgkin's lymphoma (NHL). Currently, the combination of Rituximab and chemotherapy (R-CHOP) stands as the most prevalent first-line therapy for NHL. Nevertheless, the development of new therapeutic approaches remains imperative. An increasing body of evidence highlights a novel role for IBTK in tumorigenesis and cancer growth. In this study, we aim to broaden our understanding of IBTK's function in B-lymphoma, with a particular focus on its impact on the expression of the oncogene MYC. Here, we assessed the effects of combining Rituximab with IBTK silencing on cell viability through cell cycle analysis and Annexin V assays in vitro. Furthermore, we leveraged the transplantability of Eμ-myc lymphomas to investigate whether the inhibition of IBTK could elicit anti-tumor effects in the treatment of lymphomas in vivo. Our data suggests that IBTK silencing may serve as an effective anti-tumor agent for aggressive B-Lymphomas, underscoring its role in promoting apoptosis when used in combination with Rituximab, both in in vitro and in vivo settings.